Pengaruh Tatanan Ruang dan Bentuk Kubisme pada Desain Mixed Use Building di Gunung Anyar, Surabaya - Deden Septiawan; Amir Mukmin Rachim; Ika Ratniarsih (Institut Teknologi Adhi Tama Surabaya, 2022)
As time goes by, the development of the city of Surabaya is increasing after the government completed the Merr and Oerr projects. With the project, people began to crowd the area in the once deserted Gunung Anyar area, which is now growing rapidly. However, land prices are getting more expensive, so many developers are turning to vertical buildings. Mixed Use Building is an option that can accommodate the variety of activities that crowd Gunung Anyar. Therefore, a compact space arrangement is needed and the form of cubism is chosen so that the division of space is efficient and functional. The method used in this research is descriptive method by observing the shape and space of similar comparative study objects. The application of compact cubism was chosen, especially in the processing of space and form in the Mixed Use Building design because it was influenced by the various activities of the Gunung Anyar community which were divided into several facilities such as podiums, office rentals and apartments. The results of this study are expected to create Mixed Use building facilities and infrastructure in order to give feedback to the environment in Surabaya, especially Gunung Anyar which provides residential facilities, office space and supporting facilities for the surrounding community or residents. The benefits of this research are as a forum for conveying ideas for designing mixed use buildings that are affected by the construction of the OERR and MERR projects from the Surabaya government. With the concept of cubism building, spatial planning and zoning can be created efficiently and optimally in the form of cubism buildings that adapt to limited land.